Pathological characterization and morphometric analysis of hepatic lesions in SHRSP5/Dmcr, an experimental non‐alcoholic steatohepatitis model, induced by high‐fat and high‐cholesterol diet. Issue 1 (31st March 2016) - Horai, Yasushi; Utsumi, Hiroyuki; Ono, Yuko; Kishimoto, Toshimitsu; Ono, Yuuichi; Fukunari, Atsushi
Abstract : Summary: SHRSP5/Dmcr is a newly established substrain of stroke‐prone spontaneously hypertensive rat (SHRSP). Recently, high‐fat and high‐cholesterol (HFC) diet‐fed SHRSP5/Dmcr has been reported as a novel rat model of developing hepatic lesions similar to human non‐alcoholic steatohepatitis (NASH). The aim of this study was to investigate the detailed pathological conditions induced by HFC diet in SHRSP5/Dmcr rats using molecular biological methods and morphometric analysis. SHRSP5/Dmcr rats at 6 weeks of age were fed on either HFC diet or stroke‐prone (SP) diet for 2, 4, 6, 8 and 16 weeks and histopathological changes in the liver, blood chemistry and mRNA expression levels in the liver were investigated. As evidenced by the histopathological examination of the liver of the SHRSP5/Dmcr rats, hepatic steatosis and lobular inflammation were present, with gradual increasing severity from 2 weeks after the introduction of the HFC diet. Partial hepatic fibrosis was detected at 6 weeks and spread over the entire region of the liver with more severe bridging formation by 16 weeks. The degrees of NASH‐like hepatic lesions such as steatosis (the size distribution of lipid droplets), inflammation and fibrosis were quantified by morphometric analysis. Eosinophilic inclusion bodies encountered in the hepatocytes had immunoreactivity with Cox‐4 and double‐membrane walls, identified as mega‐mitochondria. Serum ALT and bilirubins, and the mRNA expression levels related to fibrosis were closely correlated with hepatic histopathological changes. The clear feeding time‐dependent progression of NASH‐like hepatic lesion in HFC diet‐fed SHRSP5/Dmcr rats reinforced the conclusion that this strain might be a useful model of NASH and of inflammatory fibrotic liver disease.